Three-Phase Single-Carrier PWM Inverter for Isolated Grid-Tied PV Applications - Ahmed Ismail M. Ali; Mahmoud Abdallah; Takaharu Takeshita; Zuhair Muhammed Alaas (IEEE Access)
Owing to their dependency of weather conditions, distributed generation systems are integrated with utility grid through power converters. This paper proposes an isolated three-phase based flyback-inverter (TBFBI) that can be used as a central-type inverter for grid-tied PV applications. To alleviate DC-current ripples at the input side, the proposed inverter utilizes only a single LC-filter with small passive elements size, which reduces the system footprint and cost. Mathematical modeling of the TBFBI in addition to its control technique is presented in detail. Compared with other differential based converters, the proposed control technique is designed considering the least number of control loops and required sensors by using terminal voltage estimation strategy. Continuous-modulation-scheme (CMS) combined with static-linearization strategy (SLS) is utilized to diminish the low-order odd harmonics. In addition, harmonic compensation technique is utilized to eliminate negative-sequence harmonic component (NSHC) from the grid-injected currents. Also, identical three single-phase high-frequency transformers (HFTs) are designed based-on ferrite and nanocrystalline cores to compare the inverter operating efficiency. The TBFBI is experimentally validated via laboratory prototype-based 200 V, 1.6 kW, and switching frequency of 50 kHz. Experimental results of 1.6 kW power flow show that THD of the grid current is 3.95%, peak-to-peak current ripple at the input DC-side is 2.1% of the average DC input current that matches the IEEE-1547 standards for grid-tied PV applications.